Evaluación de metabolitos sanguíneos en cerdos destetados con la inclusión de probióticos en la dieta - Zapata Damacela, Alfonso Isaías (2023)
Probiotics in swine production is widely recognized as crucial in animal feed. In this regard, the study was carried out in the Acapulco farmhouse, Mocha canton, Tungurahua Province, Ecuador, where livestock reflect the action of multi-specific probiotics after weaning on productive parameters and results in blood metabolites, for which uses a Completely Random Block Experimental Design, where the distribution of each treatment is carried out randomly: T0 (Balanced), T1 (Balanced + Prob. 0.5%) and T2 (Balanced + Prob. 1%), with the use of a diet from 54 days to 89 days post weaning with an average weight of 13.35 kg in the initial phase and from 30 to 50 kg in the expected growth stage. The piglets received daily a diet with the inclusion of 1 lt. and 1.6 liters of probiotic per ton of food in the 0.5% diets, and for the 1% diet with the same amount of food, but with the inclusion of 2 and 3.3 lt. The results revealed that the T1 and T2 treatments were superior to the control in productive meters with weights of 36.55 kg and 40.12 kg. respectively, with feed conversions of 1.94 for T1 and 1.92 for T2 and with better hematological parameters with better results in T2 with: RBC of 4.03M/μL, Hematocrit of 43.16%, Hemoglobin of 15.36 g /Dl, Neutrophils 4.13 K/μL, Lymphocytes 7.36 K/μL, Monocytes 1.88 K/μL, Eosinophils 0.29 K/μL and Basophils 0.11 K/μL and in blood chemistry: Glucose 103.3333 mg/dL, Creatinine 1.1000 mg/dL, Bun 16.0000 mg/dL, Phosphorus 9.0333 mg/dL, Total Protein 8.1133 g/dL, Albumin 4.5667 g/dL, Globulin 3.7000 g/dL, which are adjusted to the reference ranges in the analysis, with the absence of diarrhea in the animals, in conclusion, the effectiveness of the inclusion of probiotics in the diet for pigs can be deduced.